KARAKTERISASI STRUKTUR BAWAH TANAH DI DAERAH POTENSI GEOTHERMAL SORIK MARAPI KABUPATEN MANDAILING NATAL DENGAN METODE MAGNETIK - Yosni Destina Simanullang; Muhammad Kadri (Universitas Negeri Medan, 2020)
The aim of the study is determine the characterization of geothermal potential area using magnetic methods and identification of rock constituent minerals by XRD test in the geothermal area of Roburan Dolok Sorik Marapi Village, Mandailing Natal Regency, Geographically the area is at coordinates 0o44'49'' SL and 99o31'32'' EL. Field data were obtained by magnetic methods using PPM (Proton Precision Magnetometer), GPS (Global Positioning System) and Geological Compass. The data is processed using Microsoft Excel, Surfer11, and Mag2dc software, so that the susceptibility is interpreted by color coding. The XRD test was carried out using a Jeol-350 Shimadzu 6100 diffractometer. Data collection was performed at 30 measurement points. The results of the study qualitatively have magnetic anomaly values ranging from -20 nT to 420 nT. The results of quantitative interpretation of A-A’ incision modeling show that the study area has a susceptibility value ranging from -0,011 to 0.0343 (in SI) and is a clastic sedimentary rock (sandstone, siltstone, claystone). Mineral constituents of geothermal rocks Sorik Marapi is quartz (O2Si) with a trigonal crystal system (hexagonal axes) with a crystal size of 9,655,267 Å. The mineral is the main constituent mineral of sandstone.